Hanover, Washington County - Carnes, Rebekah (Kansas State University, The Chapman Center for Rural Studies, 2012)
The author gives a wonderful portrayal of the Hanover, Kansas area. She delves into many aspects surrounding the town and details its settlement using maps, historic documents, and interviews with residents.
Rebekah Carnes, “Hanover, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/75.
Keywords: Big Blue River; German Community; Kansa Indians; Washington County; Pony Express; Union Pacific Railroad